Empowering ecology learning with digital storytelling: A pathway to critical and computational thinking skills - Khalida Zia; Diana Vivanti Sigit; Hanum Isfaeni (Universitas Negeri Jakarta, 2026)
Ecology learning presents complex challenges due to its interdisciplinary nature, requiring students to develop both critical and computational thinking skills. However, these higher-order cognitive abilities must be intentionally cultivated through innovative pedagogical strategies. This study developed and evaluated a digital storytelling–based learning medium designed to enhance students’ critical and computational thinking skills in ecology. The research involved 120 seventh-grade students from a public Islamic junior high school in Bekasi, Indonesia, and employed a quasi-experimental pre-test–post-test control group design. The control group received instruction through interactive PowerPoint presentations, while the experimental group used the digital storytelling medium; both groups followed a guided inquiry model. The developed media were validated by experts, yielding average scores of 74.28% (language), 77% (content), and 80% (design), indicating strong validity and feasibility. Instruments measuring critical and computational thinking were also validated and demonstrated high reliability (α = 0.83; KR-20 = 0.89). Data were analyzed using descriptive statistics and MANOVA. Results revealed significant improvements in both skills across groups, with the experimental group exhibiting greater consistency and higher final performance. Evaluation and decomposition emerged as the strongest indicators of critical and computational thinking, respectively. MANOVA confirmed a statistically significant multivariate effect (p = 0.033) of digital storytelling. These findings demonstrate that digital storytelling is a valid, feasible, and effective medium for fostering higher-order thinking in ecology learning and should be integrated into 21st-century science education